2003
DOI: 10.1677/joe.0.1780417
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and raloxifene induce apoptosis by activating p38 mitogen-activated protein kinase cascade in synthetic vascular smooth muscle cells

Abstract: Proliferation of vascular smooth muscle cells (VSMC) plays a major role as an initiating event of atherosclerosis. Although estrogen directly inhibits the proliferation of VSMC, the mechanism has not been firmly established. In addition, the effect of raloxifene on VSMC remains unknown. 17 -Estradiol (E 2 ) and raloxifene significantly inhibited the growth of VSMC under growth-stimulated conditions. Since mitogen-activated protein (MAP) kinases have been implicated in VSMC proliferation, the role of MAP kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
(32 reference statements)
1
33
0
Order By: Relevance
“…However, the ability of the ERb-E2 complex to activate rapid non-genomic mechanisms has been reported (Castoria et al 2001, Kousteni et al 2001, Geraldes et al 2003, Mori-Abe et al 2003. We recently demonstrated that E2-induced rapid signal transduction pathways in ERb-transfected HeLa cells appear to play a major role in mediating antiproliferative properties of this steroid hormone.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the ability of the ERb-E2 complex to activate rapid non-genomic mechanisms has been reported (Castoria et al 2001, Kousteni et al 2001, Geraldes et al 2003, Mori-Abe et al 2003. We recently demonstrated that E2-induced rapid signal transduction pathways in ERb-transfected HeLa cells appear to play a major role in mediating antiproliferative properties of this steroid hormone.…”
Section: Introductionmentioning
confidence: 81%
“…Geraldes and coworkers reported that E2 reduces ERK/MAPK activity through ERb stimulation in porcine smooth muscle cells (Geraldes et al 2003). Moreover, contradictory evidence on the ability of ERb to activate or inactivate Src and p38 kinases have also been reported (Castoria et al 2001, Kousteni et al 2001, Geraldes et al 2003, Mori-Abe et al 2003. We recently reported the ERb-E2 Endocrine-Related Cancer (2007) 14 153-167 www.endocrinology-journals.org complex ability to activate p38/MAPK in the ER-devoid HeLa cells transiently transfected with the ERb expression vector (Acconcia et al 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Raloxifene also inhibited the platelet-derived growth factor-induced cell proliferation in vascular smooth muscle cells, in part through inhibition of the gene expression of cyclinD1 followed by dephosphorylation of Rb mediated by ER␣ via a transcription-dependent mechanism, a so-called genomic mechanism (11), and in part by inducing apoptosis through a p38 cascade whose activation is mediated by ER␣ via a nongenomic mechanism (12). In contrast, raloxifene, like estrogen (36 -38), induced cell proliferation in vascular endothelial cells by the up-regulation of telomerase activity via post-translational regulation of Akt-dependent phosphorylation of hTERT.…”
Section: Discussionmentioning
confidence: 99%
“…Its effect is mediated by estrogen receptor (ER) ␣ via a transcription-independent mechanism, a so-called nongenomic mechanism, and is differ-* This work was supported in part by Grants-in-aid for General Scientific entially mediated by an Akt-and ERK-dependent cascade (9 -10). In vascular smooth muscle cells, raloxifene exerts an antiproliferative effect on cells treated with platelet-derived growth factor mediated by ER␣, as estrogen does, in part via a transcription-dependent mechanism, a so-called genomic mechanism (11), and in part via a nongenomic mechanism (12).…”
mentioning
confidence: 99%
“…2), in part through direct inhibition of gene expression of cyclin D1 followed by dephosphorylation of Rb and suppression of E2F activity mediated by ERa in a transcription-dependent manner, a so-called genomic mechanism [38] as reported the effect of estrogen on Rb phosphorylation [39,40], and in part due to induction of apoptosis through a p38 cascade whose activation is mediated by ERa in a transcriptionindependent manner, a so-called nongenomic mechanism [41] (Fig. 3).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%